Penerapan Content Management System untuk Website E-Commerce pada Afika Store - Siti Rafidah; Risky Rindi Andika; Sulis Sutiono; Dea Okviar Egano Napitupulu (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the application of a Content Management System (CMS) as a solution to improve the management of the Afika Store e-commerce website. With CMS implementation, it is hoped that the process of updating content, product management and user interaction can be carried out more efficiently and structured. The research method used is system development with stages of needs analysis, design, implementation and evaluation. The test results show that the CMS implemented is able to improve website performance and make it easier for admins to manage content in real-time.